2019
DOI: 10.1590/fst.28818
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting production costs and profitability of milk and dairy products in Turkey

Abstract: (Dnline) 2.6% goat milk, and 0.3% water buffalo milk (Türkiye İstatistik Kurumu, 2016). A large proportion of the milk produced in Turkey is cow milk; 52.2% of the cow milk produced is processed in industrial plants. Dut of the remaining, 21.5% is used to produce dairy products at home, 10.5% is directly sold to non-industrial buyers, 8.2% is consumed directly at home, 5.0% is used to feed animals, 2.2% is given free of charge, and 0.4% is consumed by other uses (Türkiye Ziraat Ddaları Birliği, 2011). Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In the regression analysis, it was revealed that the effect of unit cost, sales price, feed costs, fuel costs and other cost factors among the factors affecting the total profit was statistically significant. Similar to our study, in a study examining the profitability of dairy plants by using regression analysis, it was also seen that price of raw milk and dairy products were among the factors that affect the profitability of the enterprise (2). In our study it was observed that feed, fuel and other costs increased by one unit, had a positive effect on the profitability of the enterprise contrary way to the expected.…”
supporting
confidence: 87%
“…In the regression analysis, it was revealed that the effect of unit cost, sales price, feed costs, fuel costs and other cost factors among the factors affecting the total profit was statistically significant. Similar to our study, in a study examining the profitability of dairy plants by using regression analysis, it was also seen that price of raw milk and dairy products were among the factors that affect the profitability of the enterprise (2). In our study it was observed that feed, fuel and other costs increased by one unit, had a positive effect on the profitability of the enterprise contrary way to the expected.…”
supporting
confidence: 87%
“…When the production structures and product ranges produced by the enterprises operating in the milk and dairy products sector were examined, it was understood that a small number of milk buyers dominated the market. It is seen that the rest of the enterprises are small-scale producers who only produce certain products (cheese varieties) and that they work periodically (AKIN & CEVGER, 2019). This leads to a high concentration ratio in the marketing of raw milk (GÜNLÜ, 2011) as well as to complaints that the producer price of raw milk is set low because of the milk-processing firms (CA, 2018;CA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The highest cost in dairy products is of the raw material (raw milk) (Akin & Cevger, 2019). In addition, the network analysis showed that raw milk acted as the determinant and was effective in the market.…”
Section: Discussionmentioning
confidence: 99%